Nilotinib-loaded hydroxy propyl β-cyclodextrin nanosponges for improved oral bioavailability in chronic myeloid leukemia therapy - Bhagya Buela Gudipalli; Surendra AV; Ramakrishna Kakarla; Datta Maroti Pawde; Avinash Kumar G; Udaykumar Thummala; Shailendra Singh; Chakravarthi Guntupalli; Buchi N. Nalluri; Sona Muthu madaswamy; Kasi Viswanadh matte (DARU Journal of Pharmaceutical Sciences, 2026)

Targeting NF-κB and JAK/STAT pathways in rheumatoid arthritis: emerging nanocarrier-based drug delivery approaches - G. Surendra; Jeetendra Kumar Gupta; E. Susithra; A. C. Jesudoss Prabhakaran; A. Jasmine Chandra; Vijayakumar Subash; Thukani Sathanantham Shanmugarajan; Uppuluri Varuna Naga Venkata Arjun; Konatham Teja Kumar Reddy; Ramana Hechhu (Inflammopharmacology, 2026)

Generating allometric scaling relationships for aquatic species and metallic nanomaterials using nano-QSARs - Surendra Balraadjsing; Willie J.G.M. Peijnenburg; Martina G. Vijver (NanoImpact, 2026)

Predicting the dissolution of metal-based nanoparticles by means of QSPRs and the effect of data augmentation - Yuchao Song; Surendra Balraadjsing; Willie J.G.M. Peijnenburg; Martina G. Vijver (NanoImpact, 2025)

Insights into morphological and molecular diversity in grasspea (Lathyrus sativus L.) germplasm - Ramya KR; Kuldeep Tripathi; Rakesh Singh; Anjula Pandey; Ravi K. Pamarthi; Nirmal Raj Rajendran; Padmavati G. Gore; Rinky Resma Panda; Surendra Barpete; Sunil Gomashe; K. C. Bhatt (Genetic Resources and Crop Evolution, 2025)

Multicomponent Reaction Based Tolyl-substituted and Pyrene-Pyridine Conjugated Isomeric Ratiometric Fluorescent Probes: A Comparative Investigation of Photophysical and Hg(II)-Sensing Behaviors - Raghvendra Niranjan; G. Durga Prasad; Simi Achankunju; Mariyaraj Arockiaraj; Kotteswaran Velumani; Kiruthika Nachimuthu; Ashok K. Sundramoorthy; Ishita Neogi; Jothi L. Nallasivam; Venkatachalam Rajeshkumar; Surendra H. Mahadevegowda (Journal of Fluorescence, 2024)

Synergies of co-infecting pathogens, sea lice (Lepeophetheirus salmonis) and Moritella viscosa, are impacted by exposure order, and host response to initial infection - Wenlong Cai; Liang Zhong; Kathleen Parrish; Surendra Kumar; Khalil Eslamloo; Eyesun Fajei; Shona K. Whyte; Sara L. Purcell; Ladan Jahangiri; Runsheng Li; Albert Caballero Solares; Richard G. Taylor; et al. (Aquaculture, 2024)

A case study on multiple self-interactions of MSTID bands: New insights - Dipjyoti Patgiri; Rahul Rathi; Virendra Yadav; Sumanta Sarkhel; Dibyendu Chakrabarty; Subarna Mondal; M.V. Sunil Krishna; Arun K. Upadhayaya; Chiranjeevi G. Vivek; Suresh Kannaujiya; Surendra Sunda (Advances in Space Research, 2024)

A highly sensitive electrochemical sensor for Cr6+ ions detection using Ag NPs/rGO/quercetin modified glassy carbon electrode for water applications - G. Surendra Rajkumar; P. Senthil Kumar; Gayathri Rangasamy (Groundwater for Sustainable Development, 2024)

Synthesis of Di(thiophen-2-yl) Substituted Pyrene-Pyridine Conjugated Scaffold and DFT Insights: A Selective and Sensitive Colorimetric, and Ratiometric Fluorescent Sensor for Fe(III) Ions - G. Durga Prasad; Raghvendra Niranjan; Mariyaraj Arockiaraj; Venkatachalam Rajeshkumar; Surendra H. Mahadevegowda (Journal of Fluorescence, 2024)

Forest vegetation response to anthropogenic pressures: a case study from Askot Wildlife Sanctuary, Western Himalaya - Soni Bisht; G. S. Rawat; Surendra Singh Bargali; Y. S. Rawat; Abhinav Mehta (Environment, Development and Sustainability, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Investigation of jarosite-cement blends for hydration process and mechanical behavior in PQC mixes - Surendra Kumar Saini; G. D. Ransinchung; Praveen Kumar; Sonalisa Ray (Innovative Infrastructure Solutions, 2022)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Microbial and chemical quality of selected dried fish varieties available in Sri Lankan market - P. H. Ginigaddarage; I. H. W. Surendra; W. K. S. R. Weththewa; K. W. S. Ariyawansa; G. J. Ganegama Arachchi; B. K. K. K. Jinadasa; K. S. Hettiarachchi; E. M. R. K. B. Edirisinghe (Sri Lanka Journal of Aquatic Sciences, 2018)
Dried fish is one of the traditionally preserved foods in Sri Lanka.Since dried fish is often an important component of daily meal, this study was aimed to assess the quality of selected dried fish varieties in the local market. Dried fish samples of nine selected varieties were collected under three categories, viz. locally produced, imported dried fish before and after distribution to retail market. They were analyzed for microbiological and chemical parameters. Water activity of the samples was also measured. Samples were found to be negative for Escherichia coli, Staphylococcus aureus and halophilic bacteria. Aerobic Plate Count and yeast and mould count of the majority of the samples were within the acceptable limit. Histamine content exceeded 100 mg/kg level in 33% and 13% of imported and local samples respectively. Water activity of the samples was 0.05) between the analyzed parameters of all three categories.

Chitosan–Chondroitin Sulfate Based Matrix Tablets for Colon Specific Delivery of Indomethacin - Jitendra R. Amrutkar; Surendra G. Gattani (AAPS PharmSciTech, 2009)

Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (Pharmaceutical Research, 2007)

Workshop/conference report—Quantitative bioanalytical methods validation and implementation: Best practices for chromatographic and ligand binding assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (The AAPS Journal, 2007)

A first genetic linkage map of mulberry (Morus spp.) using RAPD, ISSR, and SSR markers and pseudotestcross mapping strategy - M. Venkateswarlu; S. Raje Urs; B. Surendra Nath; H. E. Shashidhar; M. Maheswaran; T. M. Veeraiah; M. G. Sabitha (Tree Genetics & Genomes, 2006)

Effect of streptozotocin-induced diabetes on oxidative energy metabolism in rat liver mitochondria—A comparative study of early and late effects - Jagannath G. Satav; Surendra S. Katyare (Indian Journal of Clinical Biochemistry, 2004)

Convective boundary layer in the region of the Monsoon Trough—A case study - Surendra S. Parasnis; Savita B. Morwal; K. G. Vernekar (Advances in Atmospheric Sciences, 1991)